Assessment of Serum Levels of Anti-Gliadin (IgA and IgG) and Interleukin-2 in Patients with Celiac Disease - Eidan, Jalal Sabr; Mubark, Hawraa Ameer (Medical Science Journal for Advance Research, 2024)
Background: Anti-gliadin antibodies (AGA) are essential for the screening of celiac disease (CD), but high AGA levels have also been seen in a number of immune-mediated cutaneous disorders, even in the absence of clinical signs of gastrointestinal illness. The study aimed to serum levels of anti-gliadin (IgA and IgG) in patients with celiac disease and factors associated with celiac disease. Materials and methods: This study is case-control design was conducted in Al-Imam Ali Hospital, Imam AL-Sadiq Hospital, and Marjan Hospital. A convenience sampling of 146 samples. The study comprised from two groups include 73 patients with celiac disease (CD), 73 healthy controls. Every participant donated 5 mL of venous blood, which was placed in gel tubes (6ml). Tubed blood is centrifuged for 10 minutes at 3000 rpm. Serum for (Anti-gliadin) is stored in Eppendorf tubes at -20 ºC until thawing on ELISA day. Results: The results reveal that patients had significantly higher mean Gliadin IgA antibody levels (5.121 ± 3.356) than controls (2.891 ± 1.438), at statistically significant P. value <0.001. Gliadin IgG antibodies were significantly higher in patients (7.312 ± 4.575) compared to controls (3.430 ± 2.111), p-value < 0.001. Furthermore, the results found that the results found that patients had significantly higher mean levels of IL-2 (28.940±11.743) than controls (21.452±3.171). Conclusions: The present study found that anti-gliadin (IgA and IgG), and IL-2 levels were higher significantly in patients with celiac disease. Furthermore, the results reveal that the sensitivity of anti-gliadin (IgG) were higher compared to anti-gliadin (IgA).